Cardiac biomarker response to intermittent exercise bouts - Carranza García, Luis Enrique; George, Keith; Serrano Ostáriz, Enrique; Casado Arroyo, Rubén; Caballero Navarro, Ana L.; Legaz Arrese, Alejandro (Georg Thieme Verlag KG, 2011)
The impact of intermittent exercise on cardiac biomarker release has not been clearly established. In experienced athletes, we examined the acute eff ect of a heavy resistance training session (n = 18 males) and an indoor soccer match (n = 21, 11 males, 10 females) on the release of cTnI, cTnT, and NT-proBNP. Biomarkers were assayed from blood samples collected at rest, immediately post- and at 1, 3, 6, 12, and 24 h post-exercise. The heavy resistance training session resulted in an increase in NT-proBNP (pre: 15 ± 17, peak post: 41 ± 56 ng L − 1 ; p = 0.001) but not in cTnI (pre: 0.024 ± 0.009, peak post: 0.025 ± 0.011 μ g L − 1 , p = 0.809) or cTnT (undetectable in all samples). The indoor soccer match led to an increase in the release of NT-proBNP (pre: 28 ± 32, peak post: 66 ± 56 ng L − 1 ; p = 0.000) and cTnI (pre: 0.026 ± 0.047, peak post: 0.033 ± 0.051 μ g L − 1 ; p = 0.008) in both males and females but not cTnT (detectable in only one subject). The current data suggest that intermittent bouts of exercise result in only modest perturbations of cardiac biomarkers with very limited evidence of myocyte injury / insult.